S21-1: “I Feel Like It Was a Springboard for Certain Changes in My Life”. A Qualitative Analysis of Health Sciences Students’ Experiences of Lifestyle Medicine Education (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: Medical school and health professions education can be stressful for students, leading them to neglect their personal wellbeing and adopt unhealthy lifestyle behaviours. The RCSI Certificate in Lifestyle Medicine was developed to provide evidence-based knowledge on six pillars of Lifestyle Medicine, and outline strategies to help students adopt healthy lifestyle behaviours which they can apply to their personal and professional lives. The aim of this study was to examine students’ perceptions of their lifestyle behaviours and preparation for clinical practice following course completion.Methods: Undergraduate and postgraduate medicine, pharmacy, physiotherapy, physician associates and research students enrolled in the online RCSI Certificate in Lifestyle Medicine between 2020 and 2022 provided survey feedback via open-ended questions on the impact of the course on their own health behaviours and professional skills, and their satisfaction with course content, delivery, and methods of assessment. Findings were analysed using reflexive inductive thematic analysis.Results: Data from 98 student evaluations were analysed. Eighty percent of students attempted to make a lifestyle change during course completion. Four themes were identified: 1) opportunity for self-reflection on own health behaviours; 2) planning a Lifestyle Medicine approach to clinical practice; 3) facilitation of self-directed learning; and 4) recommendations for enhanced delivery of educational content. Students recognised the importance of Lifestyle Medicine in their own lives and those of their patients. It was perceived as a core component of medicine and health sciences curricula and recommended to be mandatory for health care professionals.Conclusions: Findings indicate that Lifestyle Medicine education had a positive impact on student knowledge of lifestyle behaviours and prompted them to make healthier changes to their existing habits. Students recognised the importance of treating chronic disease using a Lifestyle Medicine approach and felt more confident in educating their future patients on strategies to enhance their personal health and wellbeing. Students identified that a more holistic approach to chronic disease management through Lifestyle Medicine education will assist them as future healthcare professionals.Support/Funding Source: Funded via RCSI University of Medicine and Health Sciences.Keywords: Education, health behaviours, lifestyle medicine